2021
DOI: 10.1038/s41580-021-00432-z
|View full text |Cite
|
Sign up to set email alerts
|

Structures and functions of coronavirus replication–transcription complexes and their relevance for SARS-CoV-2 drug design

Abstract: RNA genome of positive polarityAn RNA genome that has mRNA polarity and, when released from viral particles, can be used directly by host ribosomes to produce viral proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
308
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(321 citation statements)
references
References 184 publications
6
308
0
7
Order By: Relevance
“…This rate is similar than other RNA viruses such as seasonal influenza (H1N1, H3N2) with a rate between 0.6-2.0 × 10 −3 /site/year [37]. Coronaviruses encode a unique proofreading activity that is not found in other RNA viruses, this activity is encoded in the N-terminal exoribonuclease domain of nsp14, which together with nsp10 forms an RNA proofreading complex [39]. Furthermore, a recent study indicated that the mutational dynamics of SARS-CoV-2 vary in different regions.…”
Section: Relevant Characteristics Of the Sars-cov-2 Genomementioning
confidence: 55%
“…This rate is similar than other RNA viruses such as seasonal influenza (H1N1, H3N2) with a rate between 0.6-2.0 × 10 −3 /site/year [37]. Coronaviruses encode a unique proofreading activity that is not found in other RNA viruses, this activity is encoded in the N-terminal exoribonuclease domain of nsp14, which together with nsp10 forms an RNA proofreading complex [39]. Furthermore, a recent study indicated that the mutational dynamics of SARS-CoV-2 vary in different regions.…”
Section: Relevant Characteristics Of the Sars-cov-2 Genomementioning
confidence: 55%
“…Coronaviruses are a family of large positive sense single stranded (ss) RNA viruses that utilize a multi-subunit replication-transcription complex (RTC) to replicate the viral genome and synthesize sub-genomic viral mRNA transcripts within double membrane vesicles 1,2 . The RTC is composed of multiple viral non-structural proteins (Nsps), including an RNAdependent RNA polymerase (RdRp, Nsp12), RNA helicase (Nsp13), dual exonuclease/N7-Methyltransferase (Nsp14), 2'O-Methyltransferase (Nsp16), and multiple accessory/cofactor subunits (Nsp7, Nsp8, Nsp9 and Nsp10) [2][3][4][5][6] . The RTC is a leading target for new anti-viral therapeutics such as nucleotide analogues that specifically target the Nsp12 polymerase subunit [6][7][8] .…”
Section: Main Textmentioning
confidence: 99%
“…SARS-CoV-2 is an enveloped, positive sense, single-stranded RNA virus ( Kim et al, 2020 , Malone et al, 2022 ). The SARS-CoV-2 proteins consist of two large polyproteins named ORF1a and ORF1b (ORFs are proteolytically cleaved into 16 functional non-structural proteins (NSPs) ( Rohaim et al, 2021 )), four structural proteins (Envelope (E), Membrane (M), Nucleocapsid (N) spike (S) proteins)) and accessory proteins ( Kim et al, 2020 , Wu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%